Dietetic treatment lowers body mass index in overweight patients: an observational study in primary health care. Issue 5 (8th November 2013) - Tol, J.; Swinkels, I. C.; de Bakker, D. H.; Seidell, J.; Veenhof, C.
Abstract Background Greater insight into the effectiveness of usual dietetic care will contribute to the ongoing development of dietetic services. The present study examined the change in body mass index (BMI) in overweight patients after dietetic treatment in primary care, the sources of variability and factors associated with BMI change. Methods This population‐based observational study was based on data from a Dutch registration network of dietitians in primary health care. Data were derived from electronic medical records concerning 3960 overweight adult patients (BMI ≥ 25 kg m−2) who received usual care from 32 registered dietitians between 2006 and 2012. Multilevel linear regression analyses were conducted. Results Patients' BMI significantly (P < 0.001) decreased by 0.94 kg m−2 on average during treatment. An additional reduction of 0.8 kg m−2 was observed in patients treated for longer than 6 months. BMI decreased by 0.06 kg m−2 for each additional unit in initial BMI above 31.6. Most (97%) variability in BMI change was attributed to patients and 3% to dietitians. Part of the variance between patients (11%) and dietitians (30%) was explained by patient sociodemographic characteristics, nutrition‐related health aspects, initial body weight and treatment duration. Conclusions Dietetic treatment in primary care lowers BMI in overweight patients. Patients' change in BMI was rather similar between dietitians. Greater BMI reductions were observed in those with a high initial BMI and those treated for at least 6 months. Future research is necessary to study the long‐term effects of weight loss after treatment by primary healthcare dietitians, especially because many patients drop out of treatment prematurely.